Exploring new opportunities for improving AFOLU emissions reporting and the current status of AFOLU emissions for non-annex I countries - Nyawira, Sylvia S.; Mulatu, Kalkidan Ayele; Verchot, Louis V. (2022)
This policy brief has two main objectives. In a first instance, it aims to give an overview of how non-Annex I countries are currently communicating on the necessary elements (targets, monitoring plans, accounting mechanisms, implementation and achievements) for tracking their Nationally Determined Contribution (NDC) progress. Non-Annex I countries are to be understood as developing countries under the Kyoto Protocol. Contrary to Annex I countries, which are understood as developed countries and countries undergoing the process of transition to a market economy, non-Annex I countries do not have legally binding emissions reductions targets. With the existing transparency arrangements, Annex-I parties have demonstrated their ability in meeting the delivery of required information. On the other hand, non-Annex I parties have demonstrated limited experience in reporting mitigation action, which challenges not only tracking progress toward national targets but also towards global goals (Vaidyula & Rocha, 2018).